Potentially inappropriate testing for vitamin D deficiency: a cross-sectional study in Switzerland - Stefan Essig; Christoph Merlo; Oliver Reich; Maria Trottmann (BMC, 2020)
Abstract Background There is consensus that vitamin D supplementation is often indicated but population-based screening by laboratory testing for vitamin D deficiency is inadequate. Testing should be restricted to people at high risk of severe deficiency. This study describes the current lab testing for vitamin D deficiency in the adult population of Switzerland. Methods We assessed Swiss health insurance data (SWICA) for incidence of lab testing for vitamin D levels, comparing the years 2015 and 2018. Claims were analyzed for associations between lab testing and age, sex, medical indications, insurance status and geographic location in multivariable regression analyses. We also estimated the costs of vitamin D testing. Results Data from 200,043 and 200,046 persons for 2015 and 2018, respectively, were analyzed. Vitamin D level was tested in 14% of the sample population in 2015 and 20% in 2018. Testing increased by 69% for individuals aged 26-30. Testing was associated with being middle-aged to young senior citizens, female, medical indications (pregnancy, renal disease, osteoporosis, hyperparathyroidism, HIV, glucocorticoid intake), more chronic conditions, having a mandatory insurance with a low deductible, additional insurance coverage, and living in urban areas. We estimate that the total laboratory cost to mandatory insurance was about 90 million Swiss francs in 2018. Conclusions Despite recommendations for routine vitamin D supplementation, vitamin D testing of low risk individuals is common and increasing in Switzerland.